Reproductive Effects of Pyridoxal Isonicotinoyl Hydrazone in Rats: Effects on Estrus Cycle and Implantation - Sookvanichsilp, N.; Panintrarux, W.; Suksathan, S.; Rattanajarasroj, S. (Journal of Basic and Applied Pharmacology, 2015)
Pyridoxal isonicolinoyl 17ydrazone (PIH) is a highly effective compound in the management of iron overload in animals. The reproductive effects of this compound were studied in rats. PIH doses of 100, 200 and 400 mg/kg body weight given orally for 20 consecutive days produced no effects on rat’s estrus cycle. When these rats were caged with males and the PIH doses mentioned were continued feeding till day 7 of pregnancy, it was found that PIH could interfere with implantation in some rats. Male-mediated effect of PIH on implantation was also studied. Male rats were fed with PIH at doses of 100 and 200 mg/kg body weight for one month before they were housed with proestrus females. All mated rats were pregnant and no significant differences (at p = 0.05) in the number of implantation sites were found in these pregnant rats as compared to those mated with the control males.